The effect of exercises using (O.K.R.S) and (R.G.L) in the development of some compatibility capabilities of football halls (Journal of the College of Basic Education, 2020)
The effect of exercises with auxiliary tools in the development of some adaptive abilities and skillful futsalThe study aimed at preparing exercises using aids in developing some abilities For the athlete of the football halls and to know the proportion of the development of research groups The researcher assumed several hypotheses, including the existence of The hypotheses of statistical significance between the results of tribal and remote tests in all variables of research as the researcher to select the students of the first phase of the Department Physical Education and Sports Sciences in the College of Basic Education Mustansiriya for the year 2018 - 2019 and the number of (8) students as a society to discuss the selection of two divisions of the four people for the students of the first phase as a sample research 12 students from each department were selected to be two groups, one experimental and the other an officer. The sample ratio to the community was 30%. The experimental group applied exercises with two auxiliary tools (O.K.R.S.), (R.G.L ) and other auxiliary devices, which lasted for a period of 12 weeks, at a rate of 12 units per unit (90) minutes The remote tests of the compatibility abilities and the performance of the football skills of the gymnasium were then used in the process of processing the results of tribal and remote tests. The researcher reached a number of conclusions However, the exercises prepared and designed by the researcher were effective in developing the compatibility and skill capabilities of the research sample applied to them and recommended the introduction of the results of this study and use them in the development of the curriculum of football lesson For students of the Department of Physical Education and Sports Sciences of Basic Education Colleges .